Charity Connectors and Da’wah Motivation: A Phenomenological Study of Generation Z Muslim Volunteers - Jasita Apriyani; Muhammad Syaoki (Perkumpulan Ahli Manajemen Dakwah Indonesia (PAMDI), 2025)
Purpose – This study explores the meaning of volunteerism for Generation Z Muslims who are active in social-religious organizations. The present study is noteworthy not only due to the dearth of extant research on the subject, but also in light of the observed decline in social cohesion, the rise of individualism, and the pernicious influence of the virtual world. Design/methodology/approach – A phenomenological approach was used to discover the deepest meaning for Generation Z Muslims at Madrasah Relawan Bengkulu (MRB). The spiral method was used to conduct repeated interviews with eight informants who were registered as active volunteers at MRB. Non-participatory observation and documentation were used as supplementary methods. The transcription, coding and thematic analysis procedures were carried out meticulously. The systematic writing of the research results followed the thematic analysis, with the discussion exploring only two novel aspects. Findings – This study found five themes in the meaning of volunteerism: social sensitivity (altruism), emotional satisfaction, organizational activism, charitable connectors, and da'wah motivation. Two unexpected findings that emerged were: 1) the role of volunteers as charity connectors, who link donors with beneficiary communities; and 2) the self-motivation to preach, which views volunteerism as part of practizing Islam. Research implications – Social-religious organizations need to design volunteer program that can develop social involvement and spiritual commitment, in order to maintain the sustainability of volunteer participation. Originality/value – The originality of this research lies in its emphasis on the dual role of Generation Z Muslim volunteers as agents of charity and Islamic preaching. Paper type - Research paper